SENI KALIGRAFI DALAM TINJAUAN PEMIKIRAN ISLAM - Balqis Ufairo; Andini Rahmawati; Rika Ananda Yunisa (Yayasan Haiah Nusratul Islam, 2024)
Islam is a religion with the majority of its followers that is spread throughout the world. Art has an important position in Islam because the religion teaches to appreciate the three values, namely knowledge, technology, and art. Calligraphy art reflects the beauty, grandeur, and greatness of Allah which holds a significant position in Islam. This research explain the importance of calligraphy art in Islam using data from relevant textbooks and scientific article. In the Islamic perspective, calligraphy art is considered very important and has high aesthetic, philosophical, and religious values. Calligraphy art is often used to teach Islamic values and is respected for its honor to the Arabic language and the Qur’an. Calligraphy art is an integral part of Islamic culture and is a very important from of visual art.